Surgical Experience and Early Outcomes With a Slim Perimodiolar Electrode. Issue 3 (March 2019) - Friedmann, David R; Kamen, Emily; Choudhury, Baishakhi; Roland, J. Thomas
Abstract : Introduction: In 2016 the Cochlear CI532 received FDA approval and has since been the primary full-length electrode from this manufacturer implanted at our center. Our experience to date including surgical technique and early patient outcomes are reviewed here. Methods: Since 2016, this array was used as our standard full length Cochlear array, including children with normal anatomy, with 237 total implantations. Surgical experience and clinical outcomes including low frequency hearing preservation and speech perception on CNC words were analyzed in those with at least 6 months follow-up implanted through June 2017 (n = 94). Results: Speech perception scores are improving over clinical follow-up in accord with other electrode arrays. Hearing preservation is possible with a number of patients utilizing acoustic low frequency hearing in conjunction with electric stimulation from their CI. Tip fold overs were infrequent (4.6%) and always identified on intraoperative x-ray. No patients left the operating room with a tip fold over. Conclusions: Speech perception outcomes with the CI532 slim periomodiolar array are similar to other full length arrays with the added potential for at least short term preservation of residual acoustic hearing. There is a learning curve to its use and intraoperative x-rays are valuable to ensure optimal placement.